2012
DOI: 10.1159/000342380
|View full text |Cite
|
Sign up to set email alerts
|

Therapeutic Potential of ASP3258, a Selective Phosphodiesterase 4 Inhibitor, on Chronic Eosinophilic Airway Inflammation

Abstract: We investigated and compared the pharmacological effects of a PDE4 inhibitor ASP3258 (3-[4-(3-chlorophenyl)-1-ethyl-7-methyl-2-oxo-1,2-dihydro-1,8-naphthyridin-3-yl] propanoic acid), with those of roflumilast, the most clinically advanced PDE4 inhibitor known. ASP3258 inhibited human PDE4A, 4B, 4C, and 4D with respective IC50 values of 0.036, 0.050, 0.45, and 0.035 nmol/l, all approximately 3–6 times more potent than roflumilast. ASP3258 inhibited LPS-induced TNF-α production and PHA-induced IL-5 pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 45 publications
0
5
0
Order By: Relevance
“…ASP3258 (3‐[4‐(3‐chlorophenyl)‐1‐ethyl‐7‐methyl‐2‐oxo‐1,2‐dihydro‐1,8‐naphthyridin‐3‐yl] propanoic acid, Figure ) is a novel PDE4 inhibitor that inhibits PDE4 activity in rat ventricular muscle with an IC 50 of 0.28 nmol/l and exhibits at least 1000 times greater selectivity for PDE4 than PDE1, PDE2, PDE3 or PDE5 . In addition, ASP3258 exhibited anti‐asthma efficacy in two rat models with ED 50 values of 0.81 mg/kg and 0.092 mg/kg . For COPD, ASP3258 (1 mg/kg) showed efficacy as satisfactorily as roflumilast (1 mg/kg) in guinea pigs, whereas glucocorticoid prednisolone did not show any efficacy even at a higher dose (10 mg/kg) .…”
Section: Introductionmentioning
confidence: 99%
“…ASP3258 (3‐[4‐(3‐chlorophenyl)‐1‐ethyl‐7‐methyl‐2‐oxo‐1,2‐dihydro‐1,8‐naphthyridin‐3‐yl] propanoic acid, Figure ) is a novel PDE4 inhibitor that inhibits PDE4 activity in rat ventricular muscle with an IC 50 of 0.28 nmol/l and exhibits at least 1000 times greater selectivity for PDE4 than PDE1, PDE2, PDE3 or PDE5 . In addition, ASP3258 exhibited anti‐asthma efficacy in two rat models with ED 50 values of 0.81 mg/kg and 0.092 mg/kg . For COPD, ASP3258 (1 mg/kg) showed efficacy as satisfactorily as roflumilast (1 mg/kg) in guinea pigs, whereas glucocorticoid prednisolone did not show any efficacy even at a higher dose (10 mg/kg) .…”
Section: Introductionmentioning
confidence: 99%
“…The relaxation or functional antagonism exerted by PDE3 and PDE4 inhibitors was also dependent on the spasmogenic condition employed but, when the inhibitors were combined, gave a greater inhibitory effect than either inhibitor alone (Turner et al , ; Underwood et al , ; Bernareggi et al , ). The nature of the biphasic response reported with rolipram is unclear, but newer PDE4 inhibitors including roflumilast and cilomilast also produced weak or modest reversal of tone in guinea pig trachea (Bundschuh et al , ; Kobayashi et al , ). The role of PDE4 in airway smooth muscle might be dependent on the spasmogens used to contract tissues.…”
Section: Discussionmentioning
confidence: 99%
“…The most significant inhibitory effects were observed after the use of selective PDE4 inhibitors (i.e. rolipram) [12,14,16,18,[20][21][22]. Gantner et al [16] reported that TNF-α production by monocytes and macrophages is differentially regulated by PDE inhibitors.…”
Section: Discussionmentioning
confidence: 99%
“…The PDE inhibitors increase the intracellular level of cAMP and/or cGMP and, in consequence, change the activity of many cells, including phagocytic cells. Currently, the PDE4 family is the major target for the drugs affecting the immune system [8,[12][13][14]. Thus, the purpose of this study was to determine the influence of propentofylline, which inhibits principally PDE4, on the activity of phagocytic cells such as peritoneal macrophages and peripheral blood granulocytes and monocytes after in vivo administration in mice.…”
Section: Introductionmentioning
confidence: 99%